Determinan Pengungkapan Intellectual Capital Pada Perguruan Tinggi - Isna Putri Rahmawati; Afifah Ma'wa (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to determine the effect of size, complexity, age, and internationalization of universities on ICD on the official websites of PTN-BLU and PTN-BH in Indonesia. In addition, this study also aims whether there is a significant difference between the quality of ICD in PTN-BLU and PTN-BH. Methodology/approach: The number of population in this study was 47. The IC component that is used as the basis for this research uses the results of the Ulum research (2019), which consists of 60 IC items. The data analysis technique used multiple linear regression analysis and t-tests. Findings: The results showed that the size and age of the university did not affect the ICD, while the complexity and internationalization of the university had a significant positive effect on the ICD. In addition, the different test results showed a significant difference between the quality of the ICD in PTN-BLU and PTN-BH. Practical implications: PTN-BH has a higher quality IC disclosure than PTN-BLU on its official website. The most numerous components are structural capital related to PT's internal resources, such as learning systems, academics, and curricula. Originality/value: The novelty of this research regards the object of study at State Universities (PTN-BLU and PTN-BH). In addition, it also adds the internationalization variable as an independent variable.